2022
DOI: 10.1136/bcr-2022-252837
|View full text |Cite
|
Sign up to set email alerts
|

Painless thyroiditis incidentally diagnosed following SARS-CoV-2 infection

Abstract: A euthyroid woman in her 50s with papillary thyroid cancer and primary hyperparathyroidism was referred to our hospital for surgery. Her surgery was scheduled for 4 months later but was postponed because she was diagnosed with COVID-19. Five months after the first visit, she was admitted to our hospital to undergo the planned thyroid lobectomy and parathyroidectomy. Her blood tests on admission showed thyrotoxicosis, with negative thyroid-stimulating hormone receptor and thyroid-stimulating antibody. Notably, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Neck pain is characteristic of subacute thyroiditis [6], while a systematic review on subacute thyroiditis following COVID-19 showed that 69% of patients had neck pain [4]. On the other hand, a few cases of painless thyroiditis after COVID-19 have also been reported [14][15][16]. In the present case, the absence of neck pain contributed to the diagnostic delay.…”
Section: Discussionmentioning
confidence: 52%
“…Neck pain is characteristic of subacute thyroiditis [6], while a systematic review on subacute thyroiditis following COVID-19 showed that 69% of patients had neck pain [4]. On the other hand, a few cases of painless thyroiditis after COVID-19 have also been reported [14][15][16]. In the present case, the absence of neck pain contributed to the diagnostic delay.…”
Section: Discussionmentioning
confidence: 52%